2013
DOI: 10.1016/j.preghy.2013.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Chlamydia trachomatis infection increases the risk of preeclampsia

Abstract: The relationship between Chlamydia trachomatis (CT) and preeclampsia was examined longitudinally among 205 cases and 423 normotensive controls nested within the Collaborative Perinatal Project. Antibodies were analyzed at a first prenatal visit (mean 14.2 weeks) and at delivery. Prenatal infections were identified as IgG/IgM seroconversion or a four-fold rise in IgG antibody titers. Although serological evidence of incident prenatal CT infection was uncommon (n=9, 1.4%) in this general pregnant population, inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 24 publications
0
15
0
1
Order By: Relevance
“…We conducted a nested case control study of 208 singleton and primiparous preeclamptic women and 411 singleton and primiparous normotensive controls within the Collaborative Perinatal Project (CPP) [19]. Both cases and controls had no history of diabetes, cardiovascular disease or hypertension.…”
Section: Methodsmentioning
confidence: 99%
“…We conducted a nested case control study of 208 singleton and primiparous preeclamptic women and 411 singleton and primiparous normotensive controls within the Collaborative Perinatal Project (CPP) [19]. Both cases and controls had no history of diabetes, cardiovascular disease or hypertension.…”
Section: Methodsmentioning
confidence: 99%
“…Placental DNA released into the circulation of the mother and the fetus (maternal circulation) could have a role in the characteristic inflammation involved with preeclampsia [14]. In studies that looked at the connection between maternal infection and preeclampsia, it was found that the risk of preeclampsia was increased in women with urinary tract infection and periodontal disease [15][16][17].…”
Section: Inflammation And/or Infectionmentioning
confidence: 99%
“…34,35 This may be explained by the fact that the increased risk for developing preeclampsia in women with specific HLA-G alleles may be combined with CMV infection. 4 It has been stated that CMV infection impairs trophoblast differentiation and invasion. This leads in turn to down-regulate matrix metalloproteinase (MMP) activity in uterine micro vascular endothelial cells and differentiating invading cytotrophoblast.…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiology of the disease involves impaired trophoblast invasive, abnormal genetic polymorphism, vascular endothelial cell activation, immune tolerance by the maternal immune system and an exaggeration of a systematic inflammatory process. 1 Perturbation of the immune system is a central feature in the maternal generalized inflammatory response of preeclampsia; 2 among player microbial factors like Chlamydia pneumonia, 3 Chlamydia trachomatis, 4 Helicobacter pylori, 5 Human papillomavirus, 6 and cytokines like TNF-α, 7 IL-1, 8 IL-6, 9 IL-12, 10 IL-18, 11 and INF-γ 12 are thought to be involved in the pathogenesis of preeclampsia for a long time. 13,14 Data strongly focused on the alteration of the equilibration between TH1and TH2 lymphocytes in preeclamptic trophoblast, 15 in favor of an increase of TH1 profile with the consequence of defect in the expression of IL-2.…”
Section: Introductionmentioning
confidence: 99%